2013
DOI: 10.1155/2013/492893
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Risk among Asian Indians in the US: A Pilot Study

Abstract: The purpose of this pilot study was to investigate type 2 diabetes risk among Asian Indians of Kerala ethnicity living in a West Texas County of the USA. The study used a descriptive correlational design with thirty-seven adult nondiabetic Asian Indian subjects between 20 and 70 years of age. The measurement included nonbiochemical indices of obesity, family history of type 2 diabetes, length of immigration in the US, history of hypertension, physical activity pattern, and fruit and vegetable intake. The major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…We found that obesity, decreased physical activity, lack of knowledge about diabetes, and advanced age are significantly associated with low HDL in this population. AIs who have lived in the United States for greater than 10 years are more likely to have a sedentary lifestyle, increased obesity, and increased risk of diabetes type 2[ 43 ]. Ghai et al[ 44 ] compared an AI cohort to a White non-Hispanic cohort.…”
Section: Discussionmentioning
confidence: 99%
“…We found that obesity, decreased physical activity, lack of knowledge about diabetes, and advanced age are significantly associated with low HDL in this population. AIs who have lived in the United States for greater than 10 years are more likely to have a sedentary lifestyle, increased obesity, and increased risk of diabetes type 2[ 43 ]. Ghai et al[ 44 ] compared an AI cohort to a White non-Hispanic cohort.…”
Section: Discussionmentioning
confidence: 99%
“…These differences may be related to the metabolic effects of the western-style diet, or tissue resistance to insulin. One study reported that Asian Indian people have the highest incidence of DM when compared to other Asian people [ 26 ]. The Southall And Brent Revisited (SABRE) study ( n = 1007) that observed South Asian men 40–69 years of age living in North and West London for 19 years until 2011 reported a 35% incidence of DM [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite a surge in investigation of chronic diseases in Asian Americans and its subgroups, population-based studies on DM prevalence among migrant Asian Indians in the United States are limited due to small sample size, use of purposive sampling and/or specific subgroups in various regions that limits the generalizability of the results, increase measurement errors in risk factors, or lack a comparison group [21][22][23][24]. For example, a 2004 communitybased survey that included only Asian Indians living in the metro area of Georgia, Atlanta, found that 18.3% had DM [25].…”
Section: Introductionmentioning
confidence: 99%